Answer:
vertical translation of 5 units in the negative y direction, followed by a vertical translation of 7 units in the negative y direction.
Step-by-step explanation:
given f(x)=6x
f(x)=6x ---> f(x)=6x - 5 (Vertical translation by 5 units in the negative y (i.e downward) direction)
f(x)=6x - 5 ---> f(x)=6x - 5 - 7 (Vertical translation by 7 units in the negative y (i.e downward) direction)
hence it is a vertical translation of 5 units in the negative y direction, followed by a vertical translation of 7 units in the negative y direction.